A choice experiment on the willingness of households to accept power outages. (December 2016) - Abrate, Graziano; Bruno, Clementina; Erbetta, Fabrizio; Fraquelli, Giovanni; Lorite-Espejo, Azahara
Abstract: Outage cost estimation is particularly important for investment decisions related to the security and reliability of electricity supply. The heterogeneity in approaches and findings calls for more research on this topic. This paper presents a model for evaluating household Willingness to Accept (WTA) power outages in relation to expected compensation for an electricity interruption. Using a choice experiment, applied to a test sample of Italian households, we evaluate the effect of different interruption scenarios based on duration and proposed discount. The results postulate an average value of 25.37 euro/kWh of lost load for a typical Italian household. Based on survey data, the value of lost load is correlated to a set of household characteristics as well as to different durations of the hypothetical interruption. Highlights: An evaluation of the full cost generated by electric outages is proposed. A survey-based methodology relying on a choice experiment is used. A lost load value of 25.37 euro/kWh for a typical Italian household emerges.